Penelitian dan Pengembangan (Research & Development) dalam Pendidikan - Agus Rustamana; Khansa Hasna Sahl; Delia Ardianti; Ahmad Hisyam Syauqi Solihin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to describe the concept of R&D research in the field of education. This research focuses on the R&D research concept which the author breaks down into 4 sub-focuses. 1) Understanding R&D research. 2)Characteristics of R&D research. 3)R&D research objectives. 4)R&D Research Procedures. This research uses qualitative literature study methods. The conclusion of this research is that development research is a method and step to produce new productsor and improve existing products to increase effectiveness the product so that the product can be accounted for, so it can be said that this research process is more complicated and takes a long time.